(untitled) (American Journal of Technology and Applied Sciences, 2026)
Hospital pedagogy has evolved from an auxiliary service into a critical mechanism of inclusive education for learners whose health conditions disrupt regular school attendance. Hospitalization introduces unique constraints: unpredictable clinical routines, fatigue, infection control requirements, cognitive side effects of treatment, and psychosocial stress. In these conditions, traditional school-based inclusion measures are insufficient unless they are complemented by continuity mechanisms that connect hospital, home, and school learning environments. This article develops a conceptual, practice-oriented framework that integrates hospital pedagogy with digital and hybrid instructional models to ensure educational continuity during pediatric hospitalization. Using an integrative review logic and thematic synthesis of international policy sources and peer-reviewed research, the study identifies five enabling mechanisms: (1) shared governance and role clarity across hospital–school–family actors; (2) an Individualized Continuity Plan aligned with curriculum and medical constraints; (3) hybrid delivery combining bedside teaching, asynchronous micro-learning, and moderated synchronous connection to the home classroom; (4) monitoring, safeguarding, and data stewardship to protect children’s rights and privacy; and (5) reintegration pathways for return to school. The paper proposes measurable indicators (continuity rate, engagement, learning progression, psychosocial wellbeing, and technical reliability) and risk-mitigation strategies addressing digital inequality, caregiver burden, and fragmented accountability. The framework is intended to support education leaders, hospital teaching teams, and policy makers in designing resilient continuity systems that preserve learners’ educational trajectories during illness.